Students’ Perceptions, Challenges, and Opportunities in Using Kahoot! for Phrase Memorization at an Islamic Secondary School - Nisa Amalia Rachmadi; Fatimah Hidayahni Amin; Nur Aeni (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2025)
This study explores students’ perceptions of Kahoot! in an English phrase memorization program and identifies the challenges and opportunities they experienced during its implementation. Conducted at Al Mubarak Cendekia Islamic School in Makassar, Indonesia, the research employed an explanatory sequential mixed-methods design. Quantitative data were collected from 21 junior high school students through Likert-scale questionnaires, followed by qualitative interviews with selected students. Findings revealed that students’ perceptions of Kahoot! were overwhelmingly positive, with strong recognition of its role in making memorization enjoyable, interactive, and engaging. Statistical analysis demonstrated significant correlations between positive perceptions and students’ recognition of learning opportunities, while perceptions were not significantly related to reported challenges. Qualitative insights indicated that Kahoot! encouraged collaboration, motivation, and persistence but also presented difficulties, including technical issues, time constraints, and distractions. The study concludes that Kahoot! offers valuable opportunities to enhance phrase memorization in Islamic school contexts, though infrastructural and design-related challenges require careful attention. Implications are offered for teachers, schools, and policymakers in integrating gamified learning technologies.